Analysis of student needs of the mathematics club (MC) as a co-curricular activities as an effort to grow up 4C skills - Primasatya, Nurita; Imron, Ilmawati Fahmi (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2020)
In the industrial revolution 4.0, 4C’s skills (critical thinking, creative thinking, collaboration, and communication) are essential for the students. Therefore, starting from elementary school, these skills need to be cultivated. According to Permendikbud No. 23 of 2017, there are 3 activities that must carry out, namely intra-curricular, co-curricular, and extra-curricular. Like intra-curricular activities, co-curricular activities should be structured and systematic as intra-curricular that have teaching material. However, the reality is a lot of school don’t have a good preparation for doing co-curricular. Co-curricular is the activities of deepening the material (indicator) there are in intra-curricular, so the material presented in co-curricular activities must be the material that is difficult or that needs enrichment. One of the materials that requires enrichment is mathematics. It is because mathematics has contained difficult material and is usually feared by the students. This article will specifically discuss the needs of students in full-day schools whose co-curricular activities in Mathematics Club (MC) are an cultivate 4C’s skills. The method used exploratory research method. The result of this research found that Schools needed activities such as Mathematics Club because the schools had not implemented cocurricular activities optimally. Di era revolusi industry 4.0, keterampilan 4C (critical thinking, creative thinking, collaboration, and communication) penting untuk dimiliki siswa. Oleh karena itu, mulai dari tingkat sekolah dasar, kemampuan ini perlu ditumbuhkan. Sesuai Permendibud No 23 tahun 2017 terdapat 3 kegiatan yang harus dilakukan sekolah yakni intrakurikuler, kokurikuler, dan ekstrakurikuler. Layaknya kegiatan intrakurikuler, kegiatan kokurikuler seharusnya juga tersusun secara terstruktur dan sistematis disertai dengan bahan ajarnya. Namun, kenyataannya sekolah belum memiliki kesiapan yang maksimal terkait dengan perancangan dan pelaksanaan kegiatan kokurikuler tersebut. Kegiatan kokurikuler adalah kegiatan pendalaman materi (indikator) yang ada dalam kegiatan intrakurikuler, jadi materi yang disajikan dalam kegiatan kokurikuler haruslah materi yang sulit atau butuh pengayaan. Salah satu materi yang membutuhkan pengayaan adalah materi matematika. Hal ini dikarenakan matematika selalu menjadi materi yang sulit dan ditakuti siswa. Artikel ini secara spesifik akan membahas kebutuhan siswa di sekolah full day terhadap kegiatan kokurikuler mathematics club sebagai upaya menumbuhkan keterampilan 4C. Metode yang digunakan dalam penelitian ini adalah metode penelitian eksploratif dimana peneliti melakukan observasi dan wawancara secara mendalam terhadap kebutuhan sekolah terhadap kegitan kokurikuler Mathematics Club. Hasil penelitian menemukan bahwa sekolah membutuhkan kegiatan seperti Mathematics Club karena sekolah belum menerapkan kegiatan kokurikuler secara maksimal.